A New Endemic Species of Lambis Röding, 1798 from the Philippines (Mollusca: Neostromboidae: Strombidae) - Maxwell, Stephen J.; Dekkers, Aart M. (European Journal of Applied Sciences, 2022)
This paper describes a new endemic species from the central Philippines, Lambis vertriesti n. sp. and this brings the total number of Lambis species to twelve. The news species can be differentiated form other Lambis by its unique morphology. The lectotypes for Lambis lambis (Linné, 1758) and Lambis millepeda (Linné, 1758) are also designated from the syntype material in the Linnean Collection, London and the literary references provided by Linné. This new species, couples with those circumscribed, to highlight the central Philippines as a hotspot for Lambis taxa.